Phenotypic mixing of rodent but not avian hepadnavirus surface proteins into human hepatitis B virus particles. - Gerhardt, E (1995)
The virus family Hepadnaviridae comprises two genera: orthohepadnaviruses isolated from humans (hepatitis B virus [HBV]) and rodents (e.g., woodchuck hepatitis virus [WHV]) and avihepadnaviruses isolated from birds (e.g., duck hepatitis B virus [DHBV]). They carry in their envelopes two (DHBV) or three (HBV and WHV) coterminal proteins referred to as small (S), middle (M), or large (L) surface protein. These proteins are also secreted from infected cells as subviral particles consisting of surface protein and lipid (e.g., 20-nm hepatitis B surface antigen for HBV). To investigate the assembly of these proteins, we asked whether surface proteins from different hepadnaviruses are able to mix phenotypically with each other. By coexpression and coimmunoprecipitation with species-specific antibodies, we could show the formation of mixed subviral particles and disulfide-linked heterodimers between the WHV S and HBV M proteins whereas the DHBV and HBV surface proteins did not coassemble. Complementation of HBV genomes defective in expressing the S or L protein and therefore incompetent to form virions was possible with the closely related WHV S protein or a WHV pre-S-HBV S chimera, respectively, but not with the less related DHBV S or L protein or with a DHBV L-HBV S chimera. The results suggest that the assembly of HBV subviral particles and virion envelopes requires relatively precise molecular interactions of their surface proteins, which are not conserved between the two hepadnavirus genera. This contrasts with the ability of, e.g., rhabdoviruses or retroviruses, to incorporate envelope proteins even from unrelated viruses.